Dielectric properties of modified BiFeO3 ceramics - Sanjoom K. (2015)
The pure and modified BiFeO3 (BFO) ceramics (BFO doped with Sb) were prepared by a solid-state reaction method. Phase formation, microstructure, and dielectric properties were investigated. The samples showed a main phase of rhombohedral BFO. The additive inhibited grain growth, with average grain size decreasing from ∼14 μm for pure BFO to 3μm for the modified BFO samples. The dielectric constant of the modified samples tended to improve with the additive. This improvement can be related a conduction mechanism in the studied samples. © 2013 IEEE.